Criminalização da maconha: discursos proibitivos e políticas de repressão (1910-1960) - Mesquita, Francisco Pedro Trigueiro (2017)
The research aims at a historical reflection on the first post-criminalization years of marijuana in Fortaleza (CE) through the newspaper clippings of the first half of the XX century, especially the 1950s, analyzing the social historicity of relations between groups of individuals who had direct or indirect involvement with the cannabis herb culture: users, growers, traders, and the authorities performing the prohibition actions. It is also the intention of the proposal, to understand in specific, hygienic and prohibitionist aspects of the discourses on the question of marijuana in Brazil, the statements of the medical-legal scope responsible for the normatization of prohibitive instruments and the applicability of these postures in the daily life of the city via police agencies and other instruments of justice, in this part, the central problem analyzes a given set of sources: the medical works on marijuana published between 1915 and 1954, and the reports of the National Commission of Narcotics Control, gathered in the book Marijuana: Collective of Brazilian Works . Both points will be treated in keeping with the historiography of crime and drugs.